With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Re visions, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

A critique of postcolonial reason: Toward a history of the vanishing present - Spivak, Gayatri Chakravorty (Harvard University Press., 1999)
Are the “culture wars” over? When did they begin? What is their relationship to gender struggle and the dynamics of class? In her first full treatment of postcolonial studies, a field that she helped define, Gayatri Chakravorty Spivak, one of the world’s foremost literary theorists, poses these questions from within the postcolonial enclave. “We cannot merely continue to act out the part of Caliban,” Spivak writes; and her book is an attempt to understand and describe a more responsible role for the postcolonial critic. A Critique of Postcolonial Reason tracks the figure of the “native informant” through various cultural practices—philosophy, history, literature—to suggest that it emerges as the metropolitan hybrid. The book addresses feminists, philosophers, critics, and interventionist intellectuals, as they unite and divide. It ranges from Kant’s analytic of the sublime to child labor in Bangladesh. Throughout, the notion of a Third World interloper as the pure victim of a colonialist oppressor emerges as sharply suspect: the mud we sling at certain seemingly overbearing ancestors such as Marx and Kant may be the very ground we stand on. A major critical work, Spivak’s book redefines and repositions the postcolonial critic, leading her through transnational cultural studies into considerations of globality.
Keywords: 1900-1999; 1980-1989; arts; cours; discipline; fem1000; histoire; histoire et politique; international; premier cycle; périodes historiques; sciences humaines; sofia; thématiques; théories féministes; études culturelles; études littéraires; études postcoloniales

Femmes au miroir: une histoire de l'autoportrait féminin - Borzello, Frances (Thames & Hudson, 1998)
Une sélection d'autoportraits féminins empruntés à toute l'histoire de l'art, de la religieuse anonyme qui glissa son effigie dans la lettrine d'un manuscrit du XIIe siècle à Cindy Sherman et ses photogrammes révélateurs des visions stéréotypées de la femme, en passant par Sofonisba Anguissola, Artemisia Gentileschi, Elisabeth Vigée-Lebrun, Frida Kahlo, Hannah Wilke, etc.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Colonialism/postcolonialism - Loomba, Ania (Routledge, 1998)
Colonialism/Postcolonialism est un guide complet mais accessible sur les dimensions historiques, théoriques et politiques des études coloniales et postcoloniales. Ania Loomba examines the key features of the ideologies and history of colonialism, and the relationship of colonial discourse to literature. She goes on to consider the challenges to colonialism, surveying anti-colonial discourses, and recent developments in postcolonial theories and histories. Looking at how sexuality is figured in the texts of colonialism, Colonialism/Postcolonialism shows how contemporary feminist ideas and concepts intersect with those of postcolonialist thought
Keywords: approches et analyses; arts; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; ressource en ligne; thématiques; études littéraires

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Répertoire des œuvres des compositrices du Québec au XXe siècle - Labelle, Nicole (Centre de recherche en civilisation canadienne-française, 1997)
Keywords: 1900-1999; DIG; amériques; art; discipline; femmes* artistes; histoire des femmes*; histoire et politique; musique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Feminisms: An anthology of literary theory and criticism - Warhol, Robyn R.; Price Herndl, Diane (Rutgers University Press, 1997)
This volume brings together 58 previously published essays on 19th and 20th century British and North American texts that were written from the mid-1970s to 1990 by feminist literary critics. These essays cover a variety of critical perspectives, including Anglo-American, French, Marxist, structuralist, new historicist, and psychoanalytic. The 13 sections of the book cover various issues in feminist criticism: institutions, methodologies, canon, tradition, body, desire, reading, discourse, ethnicity, history, class, men, and autobiography. Each section includes essays addressing the intersections of feminist concern with questions of class, race, sexual preference, and nationality. Contributors include Barbara Christian, Sandra M. Gilbert, Susan Gubar, Helene Cixous, and Elaine Showalter
Keywords: 1900-1999; amériques; anthologie; arts; cours; cycles supérieurs; discipline; europe; fem1000; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; théories féministes; états-unis; études littéraires

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics--such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha--in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires

Fémininmasculin: le sexe de l'art. - Centre Georges Pompidou. (Passage du siècle, 1995)
Premier chapitre du Passage du siècle (les grands bilans que le Centre Georges Pompidou proposera en 1996 et 1997), cette exposition renoue avec des expériences décisives comme par exemple "Eros", organisée en 1959 par Marcel Duchamp et André Breton. A travers le titre "Féminin - Masculin, le sexe de l'art" s'exprime un double enjeu : celui de réhabiliter le terme dévalué d'une opposition inscrite dans la tradition des couples hiérarchiques de la pensée occidentale (forme/matière, vérité/mensonge, être/paraître, profondeur/surface, etc.) ; celui de montrer qu'au delà d'un simple sujet-motif artistique, le sexe est partie prenante des processus de l'art lui-même. L'ambition de cette exposition est de montrer, en dehors de toute approche chronologique, comment les productions artistiques du XXe siècle n'ont eu de cesse de venir brouiller les fatalités biologiques, anatomiques et culturelles traditionnellement liées au sexe. Aborder l'art dans la perspective de la différence sexuelle, ce n'est pas mécaniquement opposer un art "masculin" à un art "féminin", mais tenter de donner à voir comment les oeuvres se trouvent traversées par cette question, au-delà du sexe - du genre - des artistes qui les produisent. Féminin - Masculin, le sexe de l'art montrera aussi la coexistence dans ce siècle de deux généalogies artistiques concernant le sexe. L'une, à partir de Picasso, s'inscrit dans la tradition classique de la différence des sexes, conçue comme une opposition dialectique et organique du masculin et du féminin. L'autre, à partir de Marcel Duchamp, inaugure un nouveau type de relations, selon une logique asymétrique, faisant circuler les intensités masculines et féminines sur un mode proliférant qui opère une déterritorialisation des entités anatomiques, identificatoires et formelles. Les artistes de la jeune génération (tant américaine qu'européenne) semblent très sensibles à cette manière de déstabiliser les polarités traditionnelles du masculin et du féminin, mettant en oeuvre de nouvelles configurations éthiques et formelles qui se situent au-delà de la différence sexuelle, et en cela se distinguant en radicalement des positions identitaires des années 70.
Keywords: 1900-1999; LGBTQIA2+; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; exposition; har4600; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Moi, Tituba sorcière --: noire de Salem - Condé, Maryse; De Serres, Murielle; Thérien, Michel; Jean, Julie (Littératures et cultures, 1995)
Fille d'une esclave violée par un marin anglais à bord d'un vaisseau négrier, Tituba, née à la Barbade, est initiée aux pouvoirs surnaturels par Man Yaya, guérisseuse et faiseuse de sorts. Son mariage avec John Indien l'entraîne à Boston puis au village de Salem, au service du révérend Samuel Parris. Elle est emprisonnée à la suite du procès des sorcières de Salem en 1692.
Keywords: afro-féminisme; amériques; approches et analyses; arts; barbade; caraïbes; cours; discipline; féminismes noirs; histoire et politique; lit2815; premier cycle; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; états-unis; études littéraires

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Chloe plus Olivia: An anthology of lesbian literature from the seventeenth century to the present - Faderman, Lillian (Viking, 1994)
Dans Chloe Plus Olivia, Lillian Faderman ne cherche rien de moins à redéfinir radicalement quatre siècles de littérature lesbienne, répondant à un besoin longtemps négligé : une anthologie littéraire d'écrivains lesbiens des quatre derniers siècles, chaque pièce étant située dans un contexte historique et littéraire. Cet ouvrage de recherche historique propose une revue éclairante du concept changeant de « littérature lesbienne », suivi d'exemples de six genres différents : l'amitié romantique, l'inversion sexuelle, les lesbiennes exotiques et maléfiques, l'encodage lesbien, le féminisme lesbien et le féminisme post-lesbien. Faderman examine des œuvres aussi diverses que My Antonia de Willa Cather et Orlando de Virginia Woolf ; poésie de Gertrude Stein et Amy Lowell ; fiction de Carson McCullers, Helen Hull et Alice Walker. De plus, Chloe Plus Olivia contient des écrits d'hommes axés sur les relations entre femmes. Ces écrits sont inclus dans la première section du livre et ont été, à divers égards, importants pour le développement de la littérature lesbienne, puisque les hommes étaient beaucoup plus susceptibles que les femmes d'être publiés au cours des autres siècles. Il serait impossible d’identifier une seule « grande tradition » d’écriture lesbienne, car elle est en constante métamorphose, reflétant l’évolution des attitudes sociales et des voix des femmes. Chloe Plus Olivia , avec sa portée historique renforcée par la recherche personnelle de Faderman pour une définition de la littérature lesbienne, en fait le premier livre du genre ; il deviendra certainement le point de référence à partir duquel partiront toutes les études ultérieures sur la littérature lesbienne.
Keywords: arts; discipline; histoire; histoire et politique; littérature; outils; ouvrages de références; personnes lesbiennes; sciences humaines; thématiques; études littéraires

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Fatal women: Lesbian sexuality and the mark of aggression - Hart, Lynda (Princeton University Press, 1994)
Partant du lien historique entre criminalité et déviance sexuelle, Lynda Hart construit une théorie complexe et originale dans laquelle l'ombre de la lesbienne anime les représentations des femmes violentes dans la littérature, les pièces de théâtre, les films et les performances. Les chapitres détaillent cette théorie dans divers domaines, notamment : * Lulu Plays de Frank Wedekind * Thelma and Louise et Basic Instinct * l'art de la performance de Karen Finley dans le contexte des débats sur la censure * La performance des Split Britches, Lesbians Who Kill Fatal Women, est une contribution majeure à la théorie lesbienne et aux études culturelles. C'est une étude stimulante et enrichissante.
Keywords: arts; discipline; histoire et politique; personnes lesbiennes; ressource en ligne; sexualité; thématiques; violences; études culturelles; études littéraires

Les dessous des Folles alliées : un livre affriolant - Godbout, Lucie (Les éditions du remue-ménage, 1993)
Lucie Godbout, ex-Folle alliée, rappelle ici dix ans de théâtre, de cabaret, de shows tous plus drôles les uns que les autres… Un livre aussi vivant que leurs spectacles, des personnages qui interviennent dans le récit et des extraits de leur dernier show, C’est parti mon sushi!
Keywords: 1900-1999; 1980-1989; amériques; discipline; femmes* artistes; histoire des femmes*; histoire et politique; militance; périodes historiques; québec; régions géographiques; thématiques; théâtre; travail

Heavenly love?: Lesbian images in twentieth-century women's writing - Griffin, Gabriele (Manchester University Press, 1993)
Keywords: 1900-1999; arts; discipline; histoire et politique; littérature; personnes lesbiennes; périodes historiques; thématiques; études littéraires

Existe-t-il une musique dite féministe ? - Lefebvre, Marie-Thérèse (Les bâtisseuses de la Cité : actes du Colloque Les Bâtisseuses de la Cité dans le cadre de la Section d'études féministes du Congrès de l'Acfas 1992, 1993)
Keywords: 1600-1699; 1700-1799; 1900-1999; DIG; amérique du nord; amériques; arts; canada; discipline; femmes* artistes; histoire et politique; musique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Femmes, art et pouvoir et autres essais - Nochlin, Linda (Rayon art, 1993)
Plusieurs essais, rédigés à partir de 1969, qui abordent les sujets des représentations féminines dans l'art, entre la fin du XVIIIe siècle et le XXe siècle, l'érotisme et les images du féminin dans l'art du XIXe siècle et la question pourquoi n'y a-t-il pas eu de grands artistes femmes. L'auteur identifie l'idéologie dominante sur laquelle repose la place donnée aux femmes.
Keywords: approches et analyses; arts; cours; discipline; discours dominant; domination masculine; fem1000; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; rapports de domination; rapports sociaux de sexe; systèmes d'oppressions; thématiques; théories féministes

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

Sexual practice/textual theory: Lesbian cultural criticism - Wolfe, Susan J.; Penelope, Julia (B. Blackwell, 1993)
Nous vivons à l'ère postmoderniste, poststructuraliste (et, diraient certain.e.s, postféministe), à ​​une époque où le terme lesbienne pose problème, même lorsqu'il est utilisé de manière non péjorative par une lesbienne autoproclamée. Nous ne pouvons plus parler en tant qu'« individus », semble-t-il ; le faire est d’une naïveté et/ou d’une simplicité impardonnable. Nous ne pouvons parler qu'en tant que « sujets » romancés, nos identités individuelles n'existant que comme la création de textes (de quelqu'un) ou comme le résultat d'une signification. En cent ans, les sexologues allemand.e.s ont « apparu » les lesbiennes pour nous pathologiser et les poststructuralistes français.e.s nous ont « fait disparaître » pour déconstruire les catégories de sexe et de genre et « interroger » « le » sujet. Certains universitaires suggèrent que le féminisme et le postmodernisme ont de nombreux points communs. Les théoricien.nes du postmodernisme des deux côtés de l’Atlantique affirment de la même manière que leur mouvement partage un agenda politique avec le féminisme, dans la mesure où déstabiliser les relations narratives entre dominant.e et subordonné.e, contenant et contenu, c’est aussi déstabiliser les relations sociales et culturelles de domination et de confinement en dans lequel le masculin conventionnel subsume et enveloppe le féminin conventionnel. Dans le jargon actuel, le postmodemisme et le féminisme ont « problématisé les relations de genre », remettant en question le « caractère naturel » des relations de genre et considérant la relation entre les sexes comme le résultat de forces sociales, de langage et/ou de pouvoir (Giroux, 28). ). Ni « l'homme » ni la « femme » ne sont un objet ontologiquement stable, une catégorie invariable ; les deux sont construits dans l’histoire (Fuss, 3). Nous ne contesterons pas l’idée que le terme Lesbienne, pendant la brève période où il a été utilisé, a souvent été un terme d’opprobre et non d’approbation – qu’il a été utilisé linguistiquement pour signifier la déviance et même la monstruosité. Nous ne souhaitons pas non plus tomber dans le genre d’essentialisme qui supposerait que toutes les lesbiennes sont « simplement » des lesbiennes. Nous sommes membres de différentes races, classes, groupes ethniques ; collectivement, les lesbiennes souffrent de nombreuses formes d’oppression. En revanche, la philosophie postmoderne, du moins dans les formes qu'elle a prises au sein des instances du pouvoir (pédagogie académique, théorie esthétique et critique) nous semble menacer d'effacer le réel (ou, comme diraient les postmodernistes, « » matériel ») Lesbiennes. Si l’identité est construite par des textes, peut-être n’existe-t-il pas de personne (« objet ») comme lesbienne, aucune caractéristique (non construite) que partagent les lesbiennes. Si les textes et l'identité individuelle peuvent être déconstruits, peut-être que n'importe qui, même non-lesbienne, pourra « lire comme une lesbienne », comme certains l'ont suggéré. Mais s’il n’y a pas d’identité lesbienne en tant que telle, alors l’affirmation selon laquelle on « lit en tant que lesbienne » est un non-sens. Le discours postmoderniste cherche à déplacer les notions humanistes libérales du soi, du « sujet bourgeois » (H. Foster, 77, cité dans Waugh, 8). Mais comme le note Waugh (8-9), le moi unifié postulé par l’humanisme libéral n’était/n’est pas un moi féminin, et encore moins un moi lesbien. La subjectivité, historiquement construite et exprimée à travers l'équation phénoménologique soi/autre, repose nécessairement sur l'« altérité » féminine de l'« individuité » masculine. Le centre subjectif des discours socialement dominants (du « je » philosophique et rationnel de Descartes au phallique/symbolique psychanalytique de Lacan) en termes de pouvoir, d'action et d'autonomie a été un sujet « universel » qui a établi son identité à travers la marginalisation ou l'exclusion invisible de ce qu'elle a également défini comme la « féminité » (qu'il s'agisse du non-rationnel, du corps, des émotions ou du pré-symbolique). Le « féminin » devient ainsi ce qui ne peut s'exprimer parce qu'il existe en dehors du domaine de la signification symbolique. Constitué à travers un regard masculin et donc doté du mystère de celui dont le statut objectif est perçu comme absolu et définitif. Un . . . devient une femme... Dans la relation dialectique entre l'humanisme traditionnel et l'antihumanisme postmoderne apparu dans les années 1960, les femmes continuent d'être déplacées. Comment peuvent-ils aspirer, rejeter ou synthétiser un nouveau mode d’être à partir d’une thèse qui n’a jamais contenu ou exprimé ce qu’ils ont ressenti comme étant leur expérience historique ?
Keywords: amériques; anthologie; approches et analyses; arts; discipline; histoire et politique; lesbianisme; outils; ouvrages de références; personnes lesbiennes; postmodernisme; régions géographiques; sexualité; thématiques; états-unis; études littéraires

Sororophobia: Differences among women in literature and culture. - Michie, Helena (Oxford University Press, 1992)
This book looks at how differences among women have been textually represented at a variety of historical moments and in a variety of cultural contexts, including Victorian mainstream fiction, African-American mulatto novels, late twentieth-century lesbian communities, and contemporary country music. Sororophobia designates the complex and shifting relations between women's attempts to identify with other women and their often simultaneous desire to establish and retain difference. Michie argues for the centrality to feminism of a paradigm that moves beyond celebrations of identity and sisterhood to a more nuanced notion of women's relations with other women which may include such uncomfortable concepts as envy, jealousy, and competition as well as more institutionalized ideas of difference such as race and class. Chapters on literature are interspersed by "inter-chapters" on the choreography of sameness and difference among women in popular culture.
Keywords: approches et analyses; arts; classisme; discipline; histoire et politique; littérature; racisme; relations entre femmes*; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires

The persistent desire: A femme-butch reader - Nestle, Joan (Alyson publ, 1992)
Dans cette anthologie « canonique » des identités Butch-Femme, Joan Nestle retrace 200 ans d'histoire lesbienne, des lettres aux mémoires en passant par les nouvelles. Nestlé passe en revue une décennie de tentatives visant à reconstruire et à comprendre le sens et la valeur des relations butch-femme pour la lesbienne contemporaine, en s'appuyant sur l'histoire orale, la fiction, la poésie et le fantastique.
Keywords: amériques; anthologie; arts; butch/femme; discipline; désir; histoire et politique; littérature; personnes lesbiennes; poésie; ressource en ligne; régions géographiques; sexualité; thématiques; états-unis; études littéraires

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

De la mère patriarcale à la mère légendaire : Triptyque lesbien de Jovette Marchessault - Saint-Martin, Lori (Voix et Images, 1991)
Keywords: amériques; approches et analyses; arts; discipline; histoire et politique; maternité; patriarcat; personnes lesbiennes; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; études littéraires

La main tranchante du symbole : textes et essais féministes - Bersianik, Louky (Les éditions du remue-ménage, 1990)
Une anthologie au sous-titre explicite qui regroupe des textes écrits essentiellement entre 1980 et 1990, "choisis à cause de leur perspective féministe et" de "leur vision particulière de la symbolique patriarcale" (selon l'auteure, la société patriarcale est "meurtrière, hypocrite et mensongère"). Le regroupement des textes a été réalisé selon divers thèmes couvergents : l'écriture, la langue, la critique (p. 199-221), les nouvelles techniques de reproduction, la mémoire du futur, etc. Quelques textes inédits. Extraits de ##L'Euguélionne##, p. 66-91.
Keywords: amériques; antiféminisme; approches et analyses; cours; discipline; fem1000; histoire et politique; militance; mémoire collective; pratiques féministes; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Women, art, and society - Chadwick, Whitney (Thames and Hudson, 1990)
L'étude à succès acclamée de l'historienne de l'art Whitney Chadwick remet en question l'hypothèse selon laquelle les grandes femmes artistes sont des exceptions à la règle qui ont « transcendé » leur genre pour produire des œuvres d'art majeures. Tout en présentant certaines des nombreuses femmes depuis le Moyen Âge dont les contributions à la culture visuelle ont souvent été négligées, l'enquête de Chadwick réexamine les œuvres elles-mêmes et la manière dont elles ont été perçues comme marginales, souvent en référence directe au genre. Dans sa discussion sur le féminisme et son influence sur une telle réévaluation, elle aborde également les questions étroitement liées de l'ethnicité, de la classe et de la sexualité.
Keywords: LGBTQIA2+; amériques; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; régions géographiques; sexualité; thématiques; états-unis

Instabili: la question du sujet = the question of subject - Fraser, Marie; Johnstone, Lesley; Baril, Céline (Artextes, 1990)
Instabili: La question du sujet, sous la direction de Marie Fraser et Lesley Johnstone Publiés à l’occasion du 16e anniversaire de Powerhouse, sept textes et cinq projets d’artistes questionnent les multiples rapports existant entre féminisme et arts visuels, et proposent également une histoire de la galerie. L’ouvrage inclut aussi une chronologie des événements (1973-1989) qui ont marqué cette histoire. Textes de Marie Fraser, Christine Ross, Mary Kelly, Catherine Bédard, Liz Magro, Joanna Nash, Thérèse St-Gelais et Nell Tenhaaf.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; artistes féministes; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Stratégies du vertige. Trois poètes :Nicole Brossard, Madeleine Gagnon, France Théoret - Dupré, Louise (Itinéraires féministes, 1989)
Nicole Brossard, Madeleine Gagnon et France Théoret ont eu sans contredit une influence déterminante sur notre littérature. Plus qu’une étude de ces trois poètes, Stratégies du vertige nous propose de suivre un trajet amorcé dans les années 1970, au coeur des débats sur la modernité et sur l’écriture des femmes.
Keywords: amériques; arts; discipline; histoire et politique; poésie; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Le rapt de Ganymède - Fernandez, Dominique (Bernard Grasset, 1989)
"D'après la mythologie grecque, Ganymède était le plus bel adolescent vivant sur la terre. Zeus, le dieu suprême, étant tombé amoureux du jeune homme, prit la forme d'un aigle pour l'enlever et en faire son compagnon dans le ciel. Le rapt de Ganymède est resté le symbole de l'audace nécessaire à un amour qui défie les règles communes. Quand j'étais étudiant, deux mots étaient synonymes : homosexuel et paria. Aux hommes et aux femmes de ma génération a manqué la possibilité de découvrir, chez des modèles que le monde entier admire, une légitimation de goûts que l'opinion publique réprouve sous l'épithète de "contre nature". J'ai voulu montrer, d'une part que la persécution de l'homosexualité à partir du XIXe siècle s'explique par des raisons exclusivement économiques et politiques, d'autre part que certains des plus grands esprits, des meilleurs poètes et romanciers, compositeurs de musique, peintres et cinéastes de tous les temps, de Sapho à Platon, de Whitman à Cavafy, de Melville à Yourcenar, du Caravage à David, de Mozart à Schubert, d'Eisenstein à Visconti, ont tissé un réseau d'oeuvres qui peuvent servir désormais de culture, c'est-à-dire d'exemple et d'encouragement. Bien mieux que les paternes et hypocrites absolutions prononcées depuis cent ans par les psychiatres et psychanalystes, véritable imposture de notre temps, dévoilée ici dans un sottisier réjouissant. D.F." -- Site de l'éditeur
Keywords: 1800-1899; 1900-1999; DIG; LGBTQIA2+; approches et analyses; arts; beaux-arts; cinéma; cours; discipline; europe; his4860; histoire; histoire de l'art; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; littérature homosexuelle; musique; mythologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

Vision and difference femininity, feminism, and histories of art - Pollock, Griselda (Routledge, 1988)
Griselda Pollock provides concrete historical analyses of key moments in the formation of modern culture to reveal the sexual politics at the heart of modernist art. Crucially, she not only explores a feminist re-reading of the works of canonical male Impressionist and Pre-Raphaelite artists including Edgar Degas and Dante Gabriel Rossetti, but also re-inserts into art history their female contemporaries - women artists such as Berthe Morisot and Mary Cassatt. Pollock discusses the work of women artists such as Mary Kelly and Yve Lomax, highlighting the problems of working in a culture where the feminine is still defined as the object of the male gaze.
Keywords: arts; corps; cours; discipline; europe; femmes* artistes; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; représentation des femme*; régions géographiques; thématiques

In other worlds essays in cultural politics - Spivak, Gayatri Chakravorty (Routledge, 1988)
Dans cet ouvrage classique, Gayatri Chakravorty Spivak, l'une des théoriciennes de la culture les plus importantes et les plus influentes travaillant aujourd'hui, analyse la relation entre la langue, les femmes et la culture dans des contextes occidentaux et non occidentaux. Développant une intégration originale de puissantes méthodologies contemporaines - déconstruction, marxisme et féminisme - Spivak tourne ce nouveau modèle sur les grands débats de l'étude de la littérature et de la culture, assurant ainsi que In Other Worlds est devenu un outil précieux pour étudier notre propre monde et celui des autres cultures.
Keywords: 1900-1999; 1980-1989; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; histoire et politique; international; lit3220; premier cycle; périodes historiques; thématiques; théories féministes; théories littéraires; études littéraires; études postcoloniales

Femmes de la rive gauche - Benstock, Shari (Des femmes, 1987)
Femmes de la Rive gauche étudie les contributions à la vie du Paris littéraire entre 1900 et 1940 de grandes Américaines et Anglaises, telles que Djuna Barnes, Natalie Barney, Sylvia Beach, Caresse Crosby, Nancy Cunard, Hilda Doolittle, Janet Flanner, Anaïs Nin, Jean Rhys, Gertrude Stein, Edith Wharton… Écrivain.e.s, éditeurices, libraires, journalistes, tenant salon au cœur du Paris culturel, elles ont nourri de leur énergie créatrice originale le grand mouvement de la modernité. Cet essai, qui considère à la fois l’histoire littéraire et la littérature, écrit la face cachée du tissu culturel, explore la richesse d’une écriture que le modernisme a tenté de nier…. « Au lieu d’intersection de la vie et de l’art, au croisement de la mémoire et de l’histoire, à la confluence du mythe et de la biographie… j’ai retrouvé les traces de celles qui ont nourri de leur force et de leur intelligence le grand mouvement culturel moderniste. » S. B.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; cours; discipline; europe; france; his4860; histoire de l'art; histoire des femmes*; histoire et politique; littérature française; modernité; paris; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Popular culture critical readers, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. --back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Le livre de la cité des dames - De Pisan, Christine (Série "Moyen Age", 1986)
Traduction, Introduction par Éric Hicks et Thérèse Moreau À la plus italienne des Parisiennes du XVe siècle revint la gloire de défendre l’honneur des femmes : en 1405, Christine de Pizan achevait le Livre de la Cité des dames qui donnait en exemple les femmes illustres de tous les temps. Il y eut ensuite le Livre des trois vertus ou Trésor de la Cité des dames, où Christine faisait une analyse lucide et précise de la société française, vue du côté féminin, détaillant tous les «états des femmes» et donnant de chacun, depuis celui des princesses jusqu’à celui des femmes de laboureur, une vision réaliste et positive. La première, elle avait compris que les femmes avaient une place à elles dans la société politique. Née à Venise vers 1365, Christine vient, à quatre ans, vivre à Paris où son père, Thomas de Pizan, médecin et astrologue, a été appelé par Charles V. Elle défend les femmes en rassemblant un large éventail de femmes célèbres à travers l'histoire. Ces femmes sont «logées» dans la Cité des Dames, qui est en fait le livre. Alors que Pizan construit sa ville, elle utilise chaque femme célèbre comme un élément constitutif non seulement des murs et des maisons de la ville, mais aussi comme éléments constitutifs de sa thèse. Chaque femme ajoutée à la ville ajoute à l'argument de Pizan selon lequel les femmes sont des participantes valorisées dans la société. Elle plaide également en faveur de l'éducation des femmes.
Keywords: cours; discipline; europe; fem1000; histoire; histoire des femmes*; histoire et politique; incontournable; littérature; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; écriture des femmes*; éducation; études littéraires

Women artists in history: from antiquity to the 20th century - Slatkin, Wendy (Prentice-Hall, 1985)
"The careers and accomplishments of women creators in Western Civilization are described in an accessible and informative mattner in the Second Edition of Women Artists in History: From Antiquity to the 20th Century. Over sixty artists, mostly painters and sculptors, are featured in this book. Selections were based on each woman's unique and important contributions to the history of art. each artist measures up to the same rigorous standards applied to male artists in other survey texts. To understand and appreciate the achievements of these outstanding women, this volume takes a thorough look at the cultural environment in which they lived and worked, as well as the social, economic, and demographic factors that influenced their art." --From back cover
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

Une Histoire des femmes est-elle possible? - Perrot, Michelle (Rivages, 1984)
Les femmes ont-elles une histoire ? Pourquoi cette histoire n’a-t-elle pas été écrite dans le passé et pourquoi se développe-t-elle depuis une dizaine d’années ? De quelles sources dispose-t-on à cet égard et cette démarche implique-t-elle des méthodes particulières ? Que signifient « mémoire », « culture », « pouvoir » des femmes ? La catégorie de sexe est-elle, comme celle des âges, une variable historique issue des nouveaux classements induits par le développement de l’individualisme ? ou quelque chose de plus ? Voilà quelques unes des questions abordées dans ce livre qui prend en compte le changement de direction du regard historique lorsque l’on pose la question du rapport des sexes comme central. Avec la participation d’Alain Corbin, Arlette Farge, Agnès Fine, Catherine Fouquet, Geneviève Fraisse, Christiane Klapisch, Yvonne Knibiehler, Michelle Perrot, Elisabeth Ravoux-Rallo, Jacques Revel, Anne Roche, Pauline Schmitt-Pantel, Sylvie Van de Casteele, Danièle Voldman.
Keywords: arts; cours; discipline; france; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

American women artists, past and present: a selected bibliographic guide - Tufts, Eleanor (Garland reference library of the humanities, 1984)
Keywords: amériques; arts; bibliographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; pol4022; premier cycle; régions géographiques; thématiques; états-unis

L'avant-garde au feminin: Moscou, Saint-Petersbourg, Paris : 1907-1930 - Marcadé, Jean-Claude; Marcade, Valentine (Artcurial, 1983)
Paris, Artcurial, 1983, broché sous couverture illustrée, 64 pp., (27,5 x 21 cm). Exposition mai-juillet 1983. Importante illustration couleur et noir et blanc (reproductions et photographies). Biographie sommaire autour des artistes :Sonia DELAUNAY, Alexandra EXTER, Marie VASSILIEFF, Marianne WEREFKIN, Natalia GONTCHAROVA, Lioubov POPOVA, Nadiejda OUDALTSOVA, Olga ROZANOVA, Nina KOGAN, Vera PESTEL, Vera ERMOLAIEVA, Xenia ENDER, etc.
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; art moderne; arts; cours; discipline; discours dominant; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; moscou; paris; premier cycle; périodes historiques; russie; régions géographiques; saint-petersbourg; sexisme; systèmes d'oppressions; thématiques

La Québécoite: roman - Robin, Régine (Collection Littérature d'Amérique, 1983)
Sous le regard de l'Autre. Par l'auteure d'Histoire et linguistique (Colin, 1973) et d'une étude sur l'écriture juive (Le Sorbier, 1983), un récit dans lequel ce professeur d'université française, d'origine judéo-russe, qui enseigna à Montréal, Laval et Sherbrooke relate, pour le bénéfice de ses étudiants, l'histoire de sa découverte du Québec entre 1974 et 1981. Régine Robin, de formation marxiste, manifeste une attention particulière aux luttes ouvrières (grèves, etc.), politiques, idéologiques. L'éditeur parle avec justesse d'un livre d'émigrante sur l'exil, la langue et la vie d'ici. Composition en mosaïque. Inventaires, comparaisons, fragments, altérités.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; cours; discipline; disicpline; histoire et politique; immigration; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"--
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

In search of our mothers' gardens womanist prose - Walker, Alice (Harcourt Brace, 1983)
In this, her first collection of nonfiction, Alice Walker speaks out as a black woman, writer, mother, and feminist. Among the thirty-six pieces are essays about other writers, accounts of the civil rights movement of the 1960s and the anti-nuclear movement of the 1980s, and a vivid memoir of a scarring childhood injury and her daughter’s healing words.
Keywords: 1900-1999; amériques; approches et analyses; arts; cours; cycles supérieurs; discipline; droits civiques; fem1000; fem3300; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; womanist; états-unis; études littéraires

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Icon editions, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

L'autre moitié de l'avant-garde: 1910-1940: femmes peintres et femmes sculpteurs dans les mouvements d'avant-garde historiques - Vergine, Lea (Des Femmes, 1982)
L'autre moitié de l'avant-garde, 1910-1940 est une importante exposition qui s'est tenue à Milan au printemps 1980, puis à Rome, Venise, Amsterdam, Stockholm. D'une rare qualité, elle a remis à jour les démarches et recherches qui, dans la période féconde des années 1930, ont été fondamentales pour l'élaboration d'un langage contemporain. « Préparer ce travail a été, pour moi, une découverte continue : quinze mois passés à chercher dans les caves des musées, à faire ouvrir aux artistes leurs tiroirs. Rares sont les oeuvres que j'ai trouvées accrochées à un mur ! [...] L'exposition évoque les années du Blaue Reiter, du cubisme, du futurisme, du dadaïsme, du Bauhaus. Je voulais voir si les femmes avaient eu ou non, dans ces groupes, la possibilité d'être des forces motrices. Et j'ai découvert, par exemple, que dans l'avant-garde russe, les femmes ont eu un rôle tout à fait décisif...» L.V. Le catalogue rassemble ces monographies, largement illustrées des productions des femmes peintres et sculptrices, et retrace ces mouvements novateurs.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques

Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis

The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting--Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz--and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Originals: American women artists - Munro, Eleanor C. (Simon and Schuster, 1979)
Discusses the lives and work of Mary Cassatt, Georgia O'Keefe, Alice Neel, Louise Nevelson, Helen Frankenthaler, Elaine de Kooning, Sylvia Stone, and other American women artists
Keywords: 1900-1999; Biography; amériques; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Women & art: a history of women painters and sculptors from the renaissance to the 20th century - Fine, Elsa Honig (Allanheld & Schram/Prior, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

From the center: feminist essays on women's art - Lippard, Lucy R. (Dutton paperback original, 1976)
Lucy Lippard is both one of our finest critics of contemporary art and one of the most perceptive and strongest supporters of women artists. These thirty essays, written since the publication of Changing in 1971, delineate the growth of Lippard's feminism and the present status of women's art. In Lippards words: "...while I wish I could claim that this book established a new feminist criticism, all I can say is that it extends the basic knowledge of art by women, that it provides the raw material for such a development." From the Center is important, stimulating reading for all concerned with the women's art movement.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; théorie de l'art; états-unis

Women artists: recognition and reappraisal from the early Middle Ages to the twentieth century - Petersen, Karen; Wilson, J. J. (Harper colophon books ; CN 387, 1976)
Commentary on and photographs of sculpted and painted images of women created by women shed light upon feminine self-perceptions and the contributions of women artists through the centuries
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Women painters of the world: from the time of Caterina Vigri, 1413-1463, to Rosa Bonheur and the present day - Sparrow, Walter Shaw (Hacker Art Books, 1976)
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques

A history of women artists: [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present] - Munsterberg, Hugo (C. N. Potter : distributed by Crown Publishers, 1975)
A history of women artists : [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present]
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Women in the fine arts, from the seventh century B.C. to the twentieth century A.D - Clement, Clara Erskine (Hacker Art Books, 1974)
"WOMEN IN THE FINE ARTS FROM THE SEVENTH CENTURY B.C. TO THE TWENTIETH CENTURY" by Clara Erskine Clement is a historical account written in the early 20th century. The book surveys the contributions of women artists throughout history, spanning over two millennia and across multiple cultures. It aims to highlight women's roles and achievements in the fine arts, pointing out that many artists have been overlooked or forgotten despite their significant contributions. The opening of the book introduces the author's mission to gather information about women artists by reaching out to them directly, thus establishing a foundation of credibility and thoroughness for her work. Clement mentions that over a thousand women artists have been identified for this study, sharing intriguing fragments of history, such as those of ancient Greek and Roman women artist names and highlighting the cultural shifts that impacted their careers. It also critiques the lack of recorded contributions from women in the arts before the Renaissance, outlining the challenges they faced throughout different eras while paving the way for future generations of female artists. The opening sets the stage for a deeper exploration of women's artistic heritage in the following chapters. (This is an automatically generated summary.)
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Our hidden heritage: five centuries of women artists - Tufts, Eleanor (Paddington Press, 1974)
Our hidden heritage: five centuries of women artists unearths an unheralded legacy of art treasures by women artists. THrough individual biographies, the lives and work of twenty-two women artists are authoritatively described by Eleanor Tufts. These exciting portrayals provide new insights into the lives and works, the frustrations and successes of these talented women, as well as into their relationships with their contemporaries, husbands, freinds and families. Over 125 full-page reproductions of their works from major collections throughout the world demonstrate the variety and enduring quality of their art. Their lives and their work were as diverse as their cultures and their times.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Sanaaq: roman - Nappaaluk, Mitiarjuk (Stanké, 1969)
« Sanaaq est le nom de l'héroine, dont on suit, tout au long du récit, les heurs et malheurs, avant et après l'arrivée des premiers Blancs en pays inuit. À l'image de Mitiarjuk, c'est une femme forte et équilibrée, sensible et déterminée, qui nous fait découvrir de l'intérieur, comme aucun Occidental, fût-il anthropologue, n'a encore pu le faire, la vie et la psychologie des Inuits confrontés à une nature extrême, à la nécessité du partage et à l'envahissement de leur territoire par les Blancs et leur civilisation. » -- Résumé de Publications Nunavik.
Keywords: 1900-1999; 1930-1939; 1940-1949; amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; littérature; littérature inuit; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; thématiques; études littéraires

Marie de l'Incarnation - Marie de l'Incarnation; Chabot, Marie-Emmanuel (Classiques canadiens, 1962)
Keywords: 1600-1699; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Le torrent - Hébert, Anne (Beauchemin, 1950)
Un enfant prisonnier de sa mère, au cœur d’un domaine bruissant d’eaux sauvages (Le torrent) ; un instant de tendresse dérisoire, qui change à jamais la vie sage d’une ouvrière-tricoteuse (La robe corail) ; l’exode vécu comme une fête par une petite serveuse, enfin libre au milieu des dangers (Le printemps de Catherine) ; la visite quotidienne d’un homme frustré à sa sœur, qu’il espère chaque jour trouver morte (La maison de l’esplanade)... Si divers que soient les paysages, les milieux, les situations, ces nouvelles d’Anne Hébert sont toutes tendues par une même force : celle de la passion (amour ou haine) qui saisit l’être dans les premiers temps de son existence, qui ne pourra être "dite" parce que la famille, la société ou la solitude refusent cette parole, et qui ne se délivrera d’elle-même que dans la mort — meurtre ou suicide. On retrouvera, à la mesure de ces thèmes, les qualités que "Les chambres de bois" et les "Poèmes" avaient révélées : sens concret de l’instant, vigueur et brièveté de l’écriture, saveur terrienne des images et des mots.
Keywords: 1900-1999; 1990-1999; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; littérature; maternité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études littéraires

L'oublié - Conan, Laure (Beauchemin, 1936)
Ce roman historique publié en 1900 est centré sur la fondation de Montréal. il a pour héros Lambert Closse. Il a été couronné par l'Académie française (Prix Montyon, 1902). Sources documentaires de l'auteur: l'«Histoire du Canada depuis sa découverte jusqu'à nos jours» de F. X. Garneau et les «Relations des Jésuites». [SDM].
Keywords: 1600-1699; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; littérature; premier cycle; périodes historiques; québec; roman; régions géographiques; thématiques; études littéraires